Increased mortality in patients with non-functioning pituitary tumors: a study in a tertiary center - Vargas-Ortega, Guadalupe; Ramírez-García, Edgar-Manuel; Balcázar-Hernández, Lourdes; Rendón-Macias, Mario Enrique; Romero-Gameros, Carlos Alfonso; González-Virla, Baldomero; López-Félix, Blas; Zepeda, Erick; Estrada-Estrada, Eric Misael (Frontiers in Endocrinology, 2025)
Background informationMost of the studies on mortality, survival analysis and predictor variables in patients with non-functioning pituitary adenomas (NFPA) are heterogeneous and limited; and in some cases, they offer contradictory results.Patients and methodsOur objective was to analyze the survival of 749 patients (46.3% were women) with NFPA, with a mean follow-up of 60.2 months (32.9-120.6) at a tertiary center, from March 2007 to August 2023. Descriptive and inferential statistics were used. Mortality risk was determined in comparison with the Mexican population by calculating the standardized mortality ratio (SMR) with 99% confidence intervals. Survival analysis and Cox proportional hazards (HR) analysis were performed to identify possible predictors.ResultsThe overall SMR was of 8.86 (99% Confidence Interval [CI] 5.92-13.25, p<0.001), for <60 years-old patients, it was 13.77 (99% CI 7.23-26.23, p<0.001). In men, it was 7.08 (99% CI 3.92-12.80, p<0.001), and in women it was 11. 11 (99% CI 6.41-19.24, p<0.001). Regarding patients with arterial hypertension, we obtained 6.59 (99% CI 3.75-11.56, p<0.001), and with type 2 diabetes, it was 4.63 (99% CI 1.96-10.93, p<0.001). In the Cox analysis for mortality, an adjusted HR of 2.19 (95% CI 1.13-4.26, p=0.02) was observed for arterial hypertension and 1.32 (95% CI 1.00-1.75, p=0.04) for the total number of surgeries. The rest of the variables had no statistically significant association with mortality.ConclusionOur study shows a higher mortality in patients diagnosed with NFPA compared to the general population. The higher probability of death was found in the presence of predictors such as arterial hypertension and the total number of surgeries.